2014
DOI: 10.1186/1471-2369-15-165
|View full text |Cite
|
Sign up to set email alerts
|

Urinary albumin excretion and prevalence of microalbuminuria in a general Chinese population: a cross-sectional study

Abstract: BackgroundMicroalbuminuria has been shown to be a risk factor for cardiovascular and renal disease in patients with hypertension and diabetes as well as in the general population. Urinary albumin excretion over 24 h is considered a ‘gold standard’ to detect microalbuminuria. Few studies have used 24-h urinary albumin excretion to analyze the prevalence of and related factors for microalbuminuira in a general Chinese population.MethodsThis study included 1980 adults aged 18–69 years from the Shandong-Ministry o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 39 publications
1
12
1
Order By: Relevance
“…Our study showed that the prevalence of MAU was 9.0% in the study population and was much more prevalent in persons with MetS (15.1%) in particular. The prevalence of MAU in our study was moderate compared with that in other studies in China (4.1%–15%) 13 14 21–24. This varied prevalence observed in the Chinese population may be associated with different age distributions, regions and methods of defining MAU.…”
Section: Discussioncontrasting
confidence: 75%
“…Our study showed that the prevalence of MAU was 9.0% in the study population and was much more prevalent in persons with MetS (15.1%) in particular. The prevalence of MAU in our study was moderate compared with that in other studies in China (4.1%–15%) 13 14 21–24. This varied prevalence observed in the Chinese population may be associated with different age distributions, regions and methods of defining MAU.…”
Section: Discussioncontrasting
confidence: 75%
“…[8][9][10] The presence of albuminuria is associated with increased risk for adverse renal and cardiovascular outcomes in the general population and in patients with a broad array of diseases. 6,[11][12][13][14][15][16][17][18][19][20] The association between cyanotic congenital heart disease (CHD) and albuminuria has been known for more than a century. 21 However, to our knowledge, few studies 22,23 have explored this phenomenon in other subtypes of CHD in the contemporary era and in which most patients undergo surgical or catheter-based repair.…”
mentioning
confidence: 99%
“…Thus, further trials in a large series are required to determine the efficacy of STS plus irbesartan. SCr, an accurate index for renal function, also reliably predicts the risk for renal injury (Spanaus et al, 2010;Yan et al, 2014). The results of our analysis indicated that STS combined with ARBs can significantly decrease serum levels of creatinine.…”
Section: Discussionmentioning
confidence: 65%